Cardiovascular consequences caused by COVID-19: Literary review - Santos, Nathalia Charale dos (2022)
Introduction: COVID-19 is a respiratory and infectious disease caused by SARS-CoV-2, a virus with single-stranded RNA. Many cardiovascular changes have been reported caused by the agent of the viral infection. This article aims to present a literary review about cardiovascular injuries caused by COVID-19. Methodology: this study intends to discuss about modifications and cardiovascular consequences caused by COVID-19. It used the following databases: Scielo, PubMed, MEDLINE, Google Acadêmico, and Ministério da Saúde website. Articles written between 2020 and 2022 were selected to corroborate, fitting the relevance of this review. Discussion and Results: many physio-pathological mechanisms are related to cardiovascular modifications in patients with COVID-19, just as direct injury in cardiac cells and secondary injuries triggered by inflammatory, thrombotic responses and autonomic dysfunction. Conclusion: the COVID-19 infection can cause cardiovascular acute and late injuries.